324-IVIRTUAL ANGIOSCOPIC EVALUATION OF FORMATION AND PROGRESSION OF ULCER-LIKE PROJECTION IN PATIENTS WITH THROMBOSED-TYPE ACUTE AORTIC DISSECTION. (October 2014) - Miyamoto, T.; Imoto, K.; Uchida, K.; Karube, N.; Yasuda, S.; Matsuki, Y.; Masuda, M.
Abstract : Objectives: Ulcer-like projection (ULP) is an intimal lesion [penetrating atherosclerotic ulcer (PAU) or intimal tear] of thrombosed-type acute aortic dissection (AAD), and increases the risk of aortic dilatation or rupture. Virtual angioscopy by multi-detector computed tomography (MDCT) is a novel method to visualise the aortic lumen. The purpose of this study is to evaluate ULPs of AAD as intimal lesion by virtual angioscopy. Methods: From November 2010 to January 2014, 54 patients were diagnosed as thrombosed-type AAD (type B) at our hospital (mean age: 72 years, men: 59%). At acute phase, MDCTs (160 lines) were performed weekly. At chronic phase, MDCTs were performed every 6 months. Images were reconstructed to virtual angioscopy (Synapse Vincent; Fujifilm) and evaluated. Results: Mean observational period was 389 days (8–1189). MDCTs were performed an average of 4.9 times per patient. ULPs were found among 67% of patients by virtual angioscopy. Morphologically, there were two types of ULPs, round type (PAU; 66%), and slit type (intimal tear; 28 %; Fig. 1). The ULPs were observed at aortic arch (50%), descending aorta (48%), and terminal aorta (2%); 90% of slit type ULPs (intimal tear) were observed at aortic arch. Both types of ULPs were enlarged at acute phase, as mean sizes were 11, 15 and 17 mm at 0, 7 and 14 days, respectively, and at chronic phase, 39% of ULPs had disappeared (Fig. 1). Conclusion: ULPs were effectively observed by virtual angioscopy as intimal lesions. Most of the intimal tears were observed at the aortic arch. ULPs were enlarged at acute phase and tend to disappear at chronic phase.